Teachers' Strategies in Overcoming Bullying in Fifth Grade of SD Negeri 2 Tahunan - Pangastuti, Mirna; Zumrotun, Erna; Hamidaturrohmah, Hamidaturrohmah (Universitas Pendidikan Indonesia Kampus Serang, 2024)
The significant prevalence of bullying incidents in elementary schools warrants careful consideration. The impacts of bullying on an insecure educational atmosphere, as well as the psychological and physical well-being of those targeted, contribute to a perilous learning environment, hinder the educational process, and may inflict trauma on the victims. Thus, this research seeks to elucidate the strategies that fifth-grade teachers employ in addressing bullying at SD Negeri 2 Tahunan. This study employed qualitative research through a case study focused on bullying prevention strategies at SD Negeri 2 Tahunan, the designated site of this research. The strategy utilized for data collection encompassed in-depth interviews, direct observation, and analysis of school documents. Data analysis utilized a triangulation approach, incorporating the processes of data collection, reduction, presentation, and the formulation of conclusions. The findings of this study revealed that the strategies employed by teachers to address bullying at SD Negeri 2 Tahunan included 1) behavioural counselling, 2) educational initiatives on bullying through film-based learning, 3) anti-bullying socialization via ceremonies and enjoyable Friday activities, 4) establishing agreements on rules with students, 5) fostering and reinforcing religious values among students, and 6) recognizing positive behaviour through awards. The aforementioned educational strategy has the potential to significantly reduce instances of bullying at SD Negeri 2 Tahunan. Therefore, this strategy may serve as a viable solution in the pursuit of preventing and addressing bullying in various elementary schools.